Ethics in an age of terror and genocide : identity and moral choice - Monroe, Kristen Renwick, 1946- (Pt. 1. the puzzle -- Introduction -- The Holocaust and genocide -- Pt. 2. a study in contrasts -- Tony : rescuer -- Beatrix : bystander -- Kurt : soldier for the nazis -- Fritz : Nazi propagandist -- Florentine : unrepentant political Nazi -- Pt. 3. cracking the code -- The political psychology of genocide -- A theory of moral choice -- Conclusion : the psychology of difference, 2012)
What causes genocide? Why do some stand by, doing nothing, while others risk their lives to help the persecuted? Ethics in an Age of Terror and Genocide analyzes riveting interviews with bystanders, Nazi supporters, and rescuers of Jews during the Holocaust to lay bare critical psychological forces operating during genocide. Monroe's insightful examination of these moving--and disturbing--interviews underscores the significance of identity for moral choice. Monroe finds that self-image and identity--especially the sense of self in relation to others--determine and delineate our choice options.